(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The rapid proliferation of digital technologies is fundamentally reshaping how goods are moved, tracked, and managed across global supply networks. This article examines the multifaceted impact of digitalization on logistics and supply chain management (SCM), drawing on recent industry surveys, peer-reviewed research, and market data. Key areas explored include the adoption of Artificial Intelligence (AI), the Internet of Things (IoT), blockchain technology, cloud computing, and big data analytics. The evidence consistently shows that organizations that embrace digital tools achieve meaningful improvements in cost efficiency, supply chain visibility, resilience, and customer responsiveness. At the same time, the transition is not without difficulty: cybersecurity vulnerabilities, skills shortages, high implementation costs, and interoperability barriers remain persistent challenges. The article concludes with a forward-looking discussion of automation, digital twins, and the trajectory of the fully orchestrated supply chain.